Effects of ingredients of plant and animal origin on nursery pig performance - Jones, K.M.; Sotak, K.M.; Lawson, S.A.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 224 weanling pigs were used in a 34-d growth assay. The pigs were sorted by gender and ancestry, blocked by BW, and assigned to pens (7 pigs/pen and 8 pens/ treatment) in a randomized complete block design. From d 0 to 10, treatments were arranged as a 2 × 2 factorial with main effects of primary protein sources (plant vs. animal) and inclusion of soybean meal (none vs. 30%). The plant products diets had wheat gluten and corn gluten, and the animal products diets had animal plasma and fish meal as primary protein sources. All diets were formulated to be at least 120, 120, and 110% of the requirements for all essential amino acids, vitamins, and minerals, respectively, as suggested in NRC guidelines. Soybean meal replaced corn in the diet to create the diets containing soybean meal. From d 10 to 34, all pigs were fed the same cornsoybean meal–based diets to allow determination of any carryover effects (or disappearance thereof) for the diets fed for the first 10 d immediately after weaning. No interactions were observed for d 0 to 10, 10 to 34, or 0 to 34 (P > 0.12) among primary protein source and inclusion of soybean meal for ADG, ADFI, or F/G. The use of animal products increased (P < 0.02) ADG by 61% for d 0 to 10 and 7% for d 0 to 34, respectively. Soybean meal increased (P < 0.001) ADG by 31% for d 0 to 10 and tended to improve overall ADG (P < 0.07) by 5%; thus, we conclude that use of animal products (plasma protein and fish meal) and inclusion of soybean meal (30% of the diet) enhanced growth performance in weanling pigs.
Keywords: Swine; Animal protein sources; Nursery pig; Soybean meal